Robust cardiac BOLD MRI using an fMRI‐like approach with repeated stress paradigms. Issue 2 (10th March 2014) - Stalder, Aurelien F.; Schmidt, Michaela; Greiser, Andreas; Speier, Peter; Guehring, Jens; Friedrich, Matthias G.; Mueller, Edgar
<x xml:space="preserve">Abstract</x> Purpose Use repeated stress paradigms and an approach taken from neurological blood oxygen level dependent (BOLD) functional MRI (fMRI) to derive robust cardiac BOLD measurements. Methods Multiple‐repetition, single‐shot, electrocardiograph‐triggered, T2‐prepared BOLD balanced steady‐state free precession was performed during repeated long breath‐holds in 13 volunteers. Nonrigid motion correction was applied to the continuously acquired data and it was analyzed with a general linear model (GLM) taking into account the effects of the breath‐hold duration, RR interval, motion, and baseline variations. Both voxel‐ and region of interest‐based analyses were performed. Results The GLM model was able to isolate the component of the BOLD signal arising from the breath‐holds and separate it from the background effects due to the changing heart rate and motion. A significant (P < 0.05) BOLD signal increase was observed in the myocardium of healthy volunteers. Conclusion Using a recent elastic motion correction algorithm and adapted acquisition techniques, it was possible to apply fMRI‐like strategies for cardiac BOLD MRI in volunteers and derive robust BOLD measurements. The observed slight but significant oxygenation increase in the myocardium of volunteers might be explained by the vasodilator effect of increased CO2 concentration under apnea. Detection of such small physiological changes in volunteers performing breath‐holds demonstrates that the method could have potential in identifying low oxygenation regions in the myocardium of patients during stress tests. Magn Reson Med 73:577–585, 2015. © 2014 Wiley Periodicals, Inc.